Diversity and morphological characteristics of flowers in reticulatus, inodorus, and makuwa group melon (Cucumis melo) - HELFI EKA SAPUTRA; MUHAMAD SYUKUR; WILLY BAYUARDI SUWARNO; SOBIR SOBIR (Society for Indonesian Biodiversity, 2024)
Abstract. Saputra HE, Syukur M, Suwarno WB, Sobir. 2024. Diversity and morphological characteristics of flowers in reticulatus, inodorus, and makuwa group melon (Cucumis melo). Biodiversitas 25: 3130-3137. Characterization of melon (Cucumis melo L.) flowers is useful for crossing. This research aimed to obtain information about the diversity and morphological characteristics of melon flowers in the reticulatus, inodorus, and makuwa groups. Fifteen genotypes from 3 groups (5 genotypes each) were tested. There were 8 flower characters observed. Principal component and cluster analysis have been used to calculate similarity coefficients. Grouping based on flower characters was divided into 4 groups with a diversity of 52.7%. There are no morphological characteristics of flowers to characterize each group of melons. The reticulatus group has flower characteristics as follows: NMFP of 5-5.4 petals, NHFP of 5-5.2 petals, SLMF of 0.95-2.9 cm, SLHF of 0.36-1.98 cm, DMFS of 1.01-1.34 mm, DHFS of 2.57- 3.15 mm, DMF of 3.12-4.99 cm, and DHF of 8.03-8.61 cm. The inodorus group has flower characteristics as follows: NMFP of 4-5 petals, NHFP of 5 petals, SLMF of 1.34-3.18 cm, SLHF of 0.7-2.46 cm, DMFS of 1.16-1.61 mm, DHFS of 2.72-2.94 mm, DMF of 3.47-4.34 cm, and DHF of 6.56-8.15 cm. The makuwa group has flower characteristics as follows: NMFP of 5-8 petals, NHFP of 5-6 petals, SLMF of 1.32-1.98 cm, SLHF of 1.04-1.74 cm, DMFS of 1.07-1.36 mm, DHFS of 2.67- 3.86 mm, DMF of 3.31-3.85 cm, and DHF of 7.16-8.35 cm.